The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1089/neu.2018.6107
|View full text |Cite
|
Sign up to set email alerts
|

Acute Non-Convulsive Status Epilepticus after Experimental Traumatic Brain Injury in Rats

Abstract: Severe traumatic brain injury (TBI) induces seizures or status epilepticus (SE) in 20-30% of patients during the acute phase. We hypothesized that severe TBI induced with lateral fluid-percussion injury (FPI) triggers post-impact SE. Adult Sprague-Dawley male rats were anesthetized with isoflurane and randomized into the sham-operated experimental control or lateral FPI-induced severe TBI groups. Electrodes were implanted right after impact or sham-operation, then videoelectroencephalogram (EEG) monitoring was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 57 publications
(87 reference statements)
2
25
0
Order By: Relevance
“…It is well known that animals with lateral FPI lose weight, which apparently relates to brain injury-induced loss of consciousness and motor impairment, but also to nonconvulsive status epilepticus, which can last for 3-4 days. 34 Thereafter, the body weight begins to increase, eventually reaching the level of age-matched sham-operated experimental controls and naive animals. Unexpectedly, we found that the weight loss was more pronounced and the weight gain slower in TBI+ rats than in TBI− rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that animals with lateral FPI lose weight, which apparently relates to brain injury-induced loss of consciousness and motor impairment, but also to nonconvulsive status epilepticus, which can last for 3-4 days. 34 Thereafter, the body weight begins to increase, eventually reaching the level of age-matched sham-operated experimental controls and naive animals. Unexpectedly, we found that the weight loss was more pronounced and the weight gain slower in TBI+ rats than in TBI− rats.…”
Section: Discussionmentioning
confidence: 99%
“…We recently demonstrated that almost all animals with lateral FPI develop postinjury nonconvulsive status epilepticus, which is associated with both immediate (<24 hours) electrographic seizures, typically occurring within a few hours after impact, and early (<7 days) electrographic seizures, most of which are nonconvulsive and occur during D1-D4 after TBI. 34 Whether the "immediate post-impact seizure-like behavior" associates with electrographic characteristics of a seizure, thus belonging to the category of "immediate seizures," remains to be determined, however, despite the technical challenges related to EEG recordings immediately after the impact. Our findings revealed no association between acute seizure-like behavior and development of PTE, consistent with our previous study.…”
Section: Discussionmentioning
confidence: 99%
“…16 Previous studies reported that severe traumatic brain injury induced by lateral fluid-percussion injury to rats caused seizures and SE. 17,18 Co implanted in the motor cortex caused focal seizures. [19][20][21] Co binds to oxygen-binding molecules and causes functional hypoxia, triggers neuronal death, and increases expression of vascular endothelial growth factor.…”
Section: Discussionmentioning
confidence: 99%
“…The poor performance could relate to dizziness and sedation, which are well-known side effects of clomipramine in humans [61]. Recently, we found that rats with lateral FPI have non-convulsive status epilepticus lasting approximately 3 days [65]. Thus, some of our animals could still have had epileptiform activity when the clomipramine treatment was initiated.…”
Section: Discussionmentioning
confidence: 99%